Hypospadias - N. Djakovic; J. Nyarangi-Dix; A. Özturk; M. Hohenfellner (Advances in Urology)
Objective. The great possibility of variations in the clinical presentation of hypospadia, makes its therapy challenging. This has led to the development of a number of techniques for hypospadia repair. This article assesses past and present concepts and operative techniques with the aim of broadening our understanding of this malformation. Materials and Methods. The article not only reviews hypospadia in general with its development and clinical presentation as well as historical and current concepts in hypospadiologie on the basis of available literature, but it is also based on our own clinical experience in the repair of this malformation. Results and Conclusion. The fact that there are great variations in the presentation and extent of malformations existent makes every hypospadia individual and a proposal of a universal comprehensive algorithm for hypospadia repair difficult. The Snodgrass technique has found wide popularity for the repair of distal hypospadias. As far as proximal hypospadias are concerned, their repair is more challenging because it not only involves urethroplasty, but can also, in some cases, fulfil the dimensions of a complex genital reconstruction. Due to the development of modern operating materials and an improvement in current surgical techniques, there has been a significant decrease in the complication rates. Nonetheless, there still is room and, therefore, need for further improvement in this field.